Mother-daughter relationships within a Muslim community and the influence on American Muslim adolescent daughters’ health behavior - Aljayyousi-Khalil, Ghadir Fakhri (Kansas State University, 2013)
Immigrant Muslim mothers is a rapidly growing population in the United States for which there seems to be little or no information about their health values and parenting practices. Approximately 4 million adolescents in the U.S. have Arab Muslim immigrant parents. The goal of this study is to understand how adolescent girls’ health behaviors can be shaped and influenced by sociocutlural factors especially the mother-daughter relationships and the influences of living in a Muslim community in the U.S. The immigrant Muslim mother’s values (religious and cultural) that shape these relationships were examined. Next, the influence of the new dominant culture; the American culture on the mothers’ values, maternal practices and thus the adolescent daughter’s health behavior was addressed. Using criterion sampling strategy, eleven immigrant Muslim mothers and their American Muslim adolescent daughters (N=22) who were born and also raised in the United States were recruited and interviewed. The interviews were transcribed verbatim, coded, and analyzed following phenomenological research methods. Mothers in this study showed that their health values were shaped by Islam, culture origin and the acculturation factor. The majority of the mothers explained that they were more religious in the United States and some of them mentioned that they left out their culture of origin values and accept some values from the new dominant culture. Mothers in this sample explained that in order to share their values with their daughters, they needed to be close, supportive, open minded, good listeners to them. In addition, they followed different maternal practices such as: tried to be available, monitored their health behaviors, had healthy communication with them although there was imposing, and tried to model different health behaviors. However, the daughters’ perception of the mothers’ health values and maternal relationships was an important factor in determining how these values and practices could shape the daughters’ health behaviors. The results revealed that daughters who perceived that their mothers’ values and practices were shaped by the three factors were more likely to follow healthy behaviors. A theoretical model was developed. Implications for family professionals and recommendations for future research are discussed.
Keywords: Mother; Daughter; Relationship; Adolescent; Health; Islam; Health Education (0680)